PENGARUH KOMPETENSI, PENGALAMAN KERJA, DAN DISIPLIN KERJA,TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA HOTEL ASTAGINA RESORT LEGIAN BALI - Heironimus Made Dei Parwan; Ni Luh Sili Antari (Universitas Triatma Mulya, 2026)
This study aims to analyze the effect of competence, work experience, and work discipline on employee career development at Hotel Astagina Resort Legian Bali. The research employs a quantitative approach with a descriptive design. The population consists of all employees of Hotel Astagina Resort Legian Bali, totaling 90 respondents, and the sampling technique used is saturated sampling. Data collection was carried out through questionnaires using a Likert scale. The analysis technique applied in this study is multiple linear regression using SPSS version 27. The results indicate that competence, work experience, and work discipline have a positive and significant effect on employee career development. Partially, competence contributes positively to improving career opportunities, while work experience shows a stronger influence compared to other variables. Work discipline also demonstrates a significant role in supporting career advancement. Furthermore, work experience is identified as the most dominant variable influencing employee career development. These findings suggest that improving employee competence, expanding work experience, and strengthening work discipline are essential strategies to enhance career development within the organization.